Electronic structural study of defect-induced magnetism in Co doped ZnO nanostructure. (August 2020) - Bhardwaj, Richa; Chae, Keun Hwa; Goyal, Navdeep
Abstract: In this paper, Zn1- x Co x O (x = 0, 0.005, 0.01, 0.02, 0.03, and 0.05) nanostructure exhibiting room temperature ferromagnetic (RTFM) properties were synthesized via chemical solution route. Rietveld refined X-ray diffraction measurements revealed the successful incorporation of Co ions in ZnO matrix without changing the hexagonal wurtzite structure of ZnO nanocrystals and with average crystallite size in the range 35–43 nm. Photoluminescence (PL) measurements revealed the defect related red-shifted broad visible emission peak in the region 500–750 nm on doping that play a key role in ferromagnetism. Systematic magnetic and electronic structure measurements revealed that the nature of the defects and incorporated Co 2+ ions plays a significant role in attaining the ferromagnetic ordering. Near-edge X-ray absorption fine-structure (NEXAFS) and Extended edge X-ray absorption fine-structure (EXAFS) data were measured at O K -, Co and Zn K - and L 3, 2 -edges to understand the nature of defects and interactions giving rise to RTFM. These findings will be helpful in better understanding and realizing the RTFM in Co:ZnO system for spintronics and optoelectronic applications. Highlights: Single phase Co:ZnO synthesis by chemical-route with crystal size 35-43 nm. PL of Co-doped ZnO nanostructure exhibits red shift. Deconvoluted PL spectra showed the presence of defects in Co:ZnO system. The electronic structure of Co:ZnO is investigated through NEXAFS and EXAFS. Oxygen vacancies induce RTFM behavior in Co-doped ZnO samples.